EFFECTIVE METHODS OF TEACHING ENGLISH IN THE CLASSROOM - Abdulhakimova Mohlaroyim (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article presents a comprehensive guide to effective methods for teaching English in the classroom, focusing on strategies that engage students and promote meaningful language acquisition. It explores approaches such as Communicative Language Teaching (CLT) and Task-Based Learning (TBL), which emphasize real-life communication and practical tasks. The integration of technology, storytelling, and gamification is highlighted as a way to make lessons interactive and enjoyable. Additionally, the article discusses the importance of differentiated instruction, cultural immersion, and project-based learning to cater to diverse learning styles and foster critical thinking. By encouraging student autonomy and providing constructive feedback, educators can create a supportive environment that inspires confidence and a love for language learning. This article serves as a valuable resource for teachers seeking innovative ways to enhance their English teaching practices.